A hospital-based self-harm register in Mysore, South India: Is follow-up of survivors feasible in low and middle income countries? - Krishna, Murali; Majgi, Sumanth Mallikarjuna; Pradeep Kumar, Sudeep; Rajendra, Rajagopal; Heggere, Narendra; Poole, Rob; Robinson, Catherine (International Journal Of Community Medicine And Public Health, 2021)
Background: In high-income countries, dedicated self-harm surveillance systems are regarded as a key component in suicide prevention strategies, which suggests they may be important in low- and middle-income countries where rates of suicide are higher and risk factors for self-harm are different, provided they can be shown to be feasible in those settings. Methods: We established a hospital based self-harm register in Mysore, South India. A subset of participants was followed-up after two years. Results: Of the 453 who were examined at baseline, the vast majority (80%) were from rural areas, nearly a quarter were illiterate and 65 (14%) were diagnosed with depression. Compared to men, women tended to be younger, single, from rural areas, unemployed, with lower levels of educational attainment and higher levels of disability. Of the 453, 371 (80%) were successfully contacted by cellphone at 2 years. There were no significant differences in baseline variables between those followed-up and those who were not, including sociodemographic features, rates of depression, severity of disability and severity of suicidal intent. All participants reported that psychosocial assessment offered at baseline was helpful and that they would recommend assessment to others Conclusions: Findings from this study indicate that our self-harm register was a feasible and useful resource, and that contact and follow up are acceptable and feasible.